Pengaruh Persepsi Kemudahan Penggunaan, Efektivitas Dan Risiko Terhadap Minat Bertransaksi Menggunakan Aplikasi Brimo Di Bank Bri Cabang Martadinata Malang Tahun 2016- 2022 - Nindya Cahyaningrum; Jeni Susyanti; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Behavior is carried out based on someone's desire, which makes someone interested in doing it. During the transaction process, to measure a person's level of interest in performing certain behaviors, the transaction is part of the interest in the transaction that will be carried out. In this study, interest in use is influenced by several factors, namely effectiveness and risk, as well as perceptions of convenience for users. This study aims to determine how users influenced perceived ease of use, the risk, and the effectiveness of interest in using financial technology (fintech), which is measured partially and simultaneously. Explanatory or explanatory research is the type of research in this study, conducted in January 2021-2022 with a total sample of 110 BRI Bank customers. Multiple linear regression analysis is the data analysis used in this study. The results of the research in this study are: 1) There is a simultaneous influence on perceptions of ease of use on interest, 2) There is a positive and significant influence on interest and perception of ease of use, 3) There is a positive and significant influence on effectiveness and interest, 4) There is a positive and significant effect on risk on interest. Keywords : Effectiveness, Risk, Interest, Perception of Ease, Fintech